The Ruthenian Version of the Early Rus᾿ Exegesis on the Easter Canon and the Functioning of Ruthenian - Temchin, Sergei (Slavistica Vilnensis, 2020)
The Ruthenian version of the Early Rus᾿ Exegesis on John of Damascus᾿ Easter Canon is published here according to the sole known mid-16th century manuscript from the Grand Duchy of Lithuania (Saint Petersburg, The Library of the Russian Academy of Sciences, P. Dobrokhotov collection (f. 37), No. 18, f. 302‒308). The text belongs to the little known in Early Slavic studies genre of exegesis (commentaries) on hymnography and is a part of a larger (and still unpublished) set of Old Church Slavonic hymnopgraphic commentaries compiled in Pre-Mongol Kievan Rus in the late 12th‒early 13th c. From the entire set, merely the exegesis on the Easter Canon is known to be translated from Old Church Slavonic into Ruthenian.The translation confirms the earlier conclusion that Ruthenian was never used in liturgical singing in the Grand Duchy of Lithuania, since it was functioning as a lingua ad homines and clearly differed from Old Church Slavonic, which was used as a lingua ad Deum, e.g. the only Slavic Eastern Orthodox liturgical language directly addressed to God. The publication is accompanied by a description of themost important general characteristics of the Ruthenian version, which is a later and already corruptedcopy of the original translation.
Keywords: Grand Duchy of Lithuania; Ruthenian translations from Old Church Slavonic; exegesis on hymnography; John of Damascus